Avaliação da atividade ansiolítica e do possível mecanismo de ação do ácido ferúlico em zebrafish - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Anxiety disorders belong to a group of mental disorders in which the patients present excessive fear and worry. The prevalence of this pathology has been increasing over the years and tends to increase even more in the coming years. Studies have stated that oxidative stress is an important pathophysiological process involved in these disorders, as well as the deregulation of the gabaergic system. In this way, the research for substances that can reduce these symptoms becomes interesting, since the existing treatments are not always effective for the patients. Studies with ferulic acid have shown positive results to treat depressive symptoms and for this reason, the drug was chosen to have the anxiolytic activity and its possible mechanism of action evaluated in zebrafish. For this, the light/dark preference test was performed after exposure of the animals to ferulic acid, clonazepam or fluoxetine, in order to compare the behavior of the animals and verify the anxiolytic action of this substance. In order to suggest the possible mechanism of action, pre-treatment with flumazenil was performed, followed by treatment with ferulic acid and/or positive control, after whichthe same test was performed. In the light/dark preference test, the animals treated with clonazepam 0.75 mg/L, fluoxetine 10 mg/L, ferulic acid 250 and 500 mg/L, remained more time on the light side compared with untreated animals. The latency for the first entry into the dark compartment was also longer in the groups treated with fluoxetine 10 mg/L, ferulic acid 250 and 500 mg/L, when compared with the control group. In the mechanism of action test, the dwell time in the clear compartment of the animals pretreated with flumazenil 1.25 mg/L followed by treatment with ferulic acid 500 mg/L, decreased significantly compared with the group without pre-treatment. The results suggest an anxiolytic activity and mechanism of action linked to the benzodiazepine binding site of the GABAA receptor.
Evaluation of anxiolytic activity and possible mechanism of action of ferulic acid in zebrafish
Keywords: Ansiedade; Ácido ferúlico; Zebrafish; Anxiety; Ferulic acid; Zebrafish; CNPQ::CIENCIAS DA SAUDE